Work-family stressors and manufacturing firms performance : influence of work-life balance strategies - Idris Olayiwola Ganiyu; Ziska Fields; Sulaiman Olusegun Atiku (The journal of accounting and management, 2017)
Managing employees work-family pressures without resulting in negative influence on employees contributions and performance remains a challenge to human resource practitioners in the manufacturing industry. Efforts geared towards tackling this challenge have led to the development of various work-life balance strategies in the industry. Yet, the effectiveness of the developed work-life balance strategies to manage employees work-family stressors and performance remains an issue. This study investigated the influence of work-life balance strategies on the interplay between work-family stressors and performance in the manufacturing industry. A quantitative survey research design was adopted. Data were collected from 312 employees in the manufacturing firms operating in the Lagos metropolis using a simple random sampling technique. A self-report questionnaire was used for data collection. The preliminary data analysis was done using the Statistical Package for Social Sciences, version 24. The variance-based Structural Equation Modelling was run using SmartPLS 3.3 for hypothesis testing and for path analysis of the structural model. This study found that work-life balance strategies fully mediate the relationship between work stressors and manufacturing firms performance. It is recommended that the family aspect of the work-life balance strategies be redesigned to reduce the negative influence of family stressors on manufacturing firms performance.
2668125-0; 2392-8778; The journal of accounting and management; 718053745